YourNow : Daimler´s and BMW´s joint road towards new mobility? - Scherer, Lisa Maria (2020)
In the late 1990s the Dynamic Capabilities framework by Teece et al. (1997) shifted the focus of strategic management to an individual company’s resources and its ability to adapt them to external market trends. Refined by Barreto (2010), this resource-based view serves as a theoretical framework for this thesis, which aims at examining the development of a strategic, technological partnership between two established industrial companies. Hereby, Daimler and BMW, two of Germany’s leading automotive manufacturers are used as a real-world example in the form of a case study. The case depicts the current developments in the automotive industry and the opportunities available in the field of new mobility for traditional manufacturing companies. It outlines Daimler’s and BMW’s historical milestones and their path towards their mobility joint venture YourNow, launched in early 2019. From a strategic point of view, the case highlights the companies’ motives for the joint venture. It analyzes the exogenous shocks the companies faced, urging the former rivals to cooperate. Furthermore, the case evaluates the joint venture’s capabilities to succeed in the highly competitive mobility market as of mid 2020.